CHOREOGRAPHY AND PICTORIAL MEDIA OF COUGH ETHICS CAN IMPROVE THE KNOWLEDGE, ATTITUDE, AND SKILLS OF ELEMENTARY SCHOOL CHILDREN IN BENGKULU CITY - Linda Linda; Reka Lagora Marsofely (Proceeding B-ICON, 2022)
Problem: Infectious disease is one of the health problems in the world, including in developing countries such as Indonesia. Environmental and cultural conditions in this country significantly affect the incidence of infection, stone disease, and its derivatives, which are still in the top ten deaths in Indonesia. This condition results from the public's lack of awareness of the dangers of chronic cough. One strategy that can be used to attract children's attention is using audio and visual or combining dance and song or choreography, also known as dance composition, which is the art of making/designing structures or grooves so that they become a pattern of movements. The term fare composition can also include navigation or connection to the system of the movement. In choreography, it is used to understand a tariff arrangement that can be analyzed from content, form, and technique. The aim of the research: This study aims to determine the effect of choreography and illustrated media on cough etiquette on increasing elementary school children's knowledge, attitudes, and skills in the city of Bengkulu. Research methods: This type of research is a quantitative study with a quasi-experimental pre and post-test design with a control group. The group consisted of elementary school students who were given promotions on cough etiquette through choreography. In contrast, the control group was elementary school students who were given promotions on cough etiquette through illustrated cartoons. The population in this study were all elementary school students in Bengkulu City who found 26780 people. Results: The results of the bivariate analysis using the Wilcoxon test showed that after the intervention by giving a cough etiquette choreography video, the value is 0.003 < 0.05, indicating a difference in respondents' knowledge before and after choreographic video media. Meanwhile, knowledge after intervention by giving cough etiquette media values ??was obtained at 0.000 <0.05, which means there is a difference in respondents' knowledge before and before being given pictorial media. Conclusion: There is no difference between the effect of choreography and Media with cough etiquette on elementary school children's knowledge, attitudes, and skills in the city of Bengkulu.